In search of academic voice: the impact of instructional grouping configurations on English language learner academic language production - Brooks, Kathryn A. (Kansas State University, 2006)
This study utilized an ecobehaviorial approach to investigate the relationship between English language learner language use in middle school content area classrooms and instructional grouping configurations. The participants in the study included 28 native Spanish-speaking students who attended urban middle schools. These students were all identified as being English language learners (ELL) in need of English as a second language support services. This study used the Ecobehavioral System for the Complex Recording of Interactional Bilingual Environments (ESCRIBE) software to record data regarding contextual factors and ELL student behavior using 15 second momentary time sampling in mathematics, social studies, science, reading, and language arts classes. The program analyzed this data to determine conditional probabilities of various student behaviors given each contextual factor. The focus contextual factor of this study was instructional grouping configurations: whole class, small group, one-to-one, and individual instruction. The focus student academic responses included academic language production (writing, reading aloud, and talk academic), academic language reception (reading silently, student attention, and other academic), and other non-academic responses. In this study, the participants were most likely to produce academic language during small group and one-to-one instruction. They were least likely to engage in academic talk during whole class and individual instruction. If teachers want to encourage ELL students to produce academic language, they should consider using more small group and one-to-one instructional grouping configurations.
Keywords: ESL; English language learner; classroom interaction; academic language; ecobehavioral; middle school; Education, Bilingual and Multicultural (0282); Education, Curriculum and Instruction (0727); Education, Language and Literature (0279)